'From Choice to Chance': choice-based letting use in forced tenant relocations in New South Wales, Australia. Issue 8 (14th September 2019) - Melo Zurita, Maria de Lourdes; Ruming, Kristian
Abstract: The redevelopment of large social housing estates has emerged as a central policy response to address housing affordability and social housing crises in Australia. These projects, often done in partnership with the private sector, are seen as opportunities to leverage government land assets and increase densities to expand social and private housing stock. While extensive research has been conducted on the rationale and processes of estate renewal, less attention has been paid to tenant relocation practices. This is the focus of this article. In particular we explore the New South Wales Government's use of a choice-based letting program called 'My Property Choice' (MPC) that involves tenants bidding via a ballot system for available social housing properties. We argue, despite policy rhetoric emphasising resident 'choice', MPC emerges as a chance-based process for tenants seeking to 'win' their desired relocation destinations.